2014
DOI: 10.1126/scitranslmed.3010444
|View full text |Cite
|
Sign up to set email alerts
|

Public Biobanks: Calculation and Recovery of Costs

Abstract: A calculation grid developed by an international expert group was tested across biobanks in six countries to evaluate costs for collections of various types of biospecimens. The assessment yielded a tool for setting specimen-access prices that were transparently related to biobank costs, and the tool was applied across three models of collaborative partnership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 7 publications
1
43
0
1
Order By: Relevance
“…19 Furthermore, in a study published in 2014, Clément et al assessed the real costs of operational processes in 20 European and US biobanks handling either human samples or microorganisms implicated in human health and disease. 20 The estimated real costs substantially exceeded the fees charged by the biobank. For example, real costs for a tumor approximated €1,500 ($1,680), while those for DNA extracted from blood were estimated at €460 ($515).…”
Section: Discussionmentioning
confidence: 99%
“…19 Furthermore, in a study published in 2014, Clément et al assessed the real costs of operational processes in 20 European and US biobanks handling either human samples or microorganisms implicated in human health and disease. 20 The estimated real costs substantially exceeded the fees charged by the biobank. For example, real costs for a tumor approximated €1,500 ($1,680), while those for DNA extracted from blood were estimated at €460 ($515).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] Analyses have found that, at most, 5%-25% of operation costs could be recovered through distribution fees because the actual cost of collecting and distributing tissue is prohibitive for the requesting researcher. 22,23 Even with aggressive marketing, the demand for biospecimens varies and is irregular based on individual researcher needs, research funding, and availability of required samples. 24 Furthermore, even in ideal circumstances, only a percentage of collected samples will be distributed, which would necessitate adding non-distributed specimen collection and storage costs into the cost recovery fees, making biospecimens even more expensive.…”
Section: The Biobank Core Facilitymentioning
confidence: 99%
“…Additionally, this allows inclusion of clinical samples that have been processed for biobanking, or to use such samples for replication or validation. Biobanks collect large numbers of samples such as tissues or DNA (deoxyribonucleic acid) and the associated patient information, which is highly valuable for retrospective biomarker studies [69]. Exploratory screens for candidate biomarkers mainly rely on the use of patient specimens, which are obtained in small quantities, while also biobanks often contain limited quantities of patient material.…”
Section: Introductionmentioning
confidence: 99%